Expression of NCAM and OCIAD1 in well-differentiated thyroid carcinoma: correlation with the risk of distant metastasis. Issue 3 (12th November 2011) - Yang, An-Hang; Chen, Jui-Yu; Lee, Chen-Hsen; Chen, Jun-Yi
Abstract : Aims: The biomarkers representing the metastatic potential of well-differentiated thyroid carcinoma remain to be established. A study was undertaken to find whether the expression status of neural cell adhesion molecule (NCAM) and/or ovarian cancer immunoreactive antigen domain containing 1 (OCIAD1) is associated with the metastatic potential of differentiated thyroid carcinoma. Methods: NCAM and OCIAD1 were analysed by immunohistochemistry on tissue microarrays. Results: Among 214 well-differentiated thyroid carcinomas, 68 patients had distant metastases. Immunohistochemical analyses showed that the majority of benign thyroid lesions expressed NCAM while a significant proportion of thyroid carcinomas lost or had reduced NCAM expression. Both follicular and papillary carcinomas with distant metastasis had a significantly higher frequency of preserving NCAM expression. Hierarchical clustering analysis showed that OCIAD1 had significant differential expression between benign and malignant thyroid lesions. The overall metastatic-to-localised tumour ratio was higher in NCAM-expressing clusters, but the difference between ratios of OCIAD1-positive and OCIAD1-negative subclusters was not significant. Conclusions: These analyses suggest that the preservation of NCAM expression in well-differentiated thyroid carcinoma is an indicator for a higher risk of distant metastasis. OCIAD1 is a potential biomarker of thyroid carcinoma but had no significant additive effect on the risk of distant metastasis. Further elucidation of the molecular mechanisms underlying the NCAM-mediated cellular processes will be beneficial for the development of effective treatments against the metastasis of thyroid carcinoma.